Federal Constitutional Court of Pakistan: Prospects and Lessons from Indonesia - Ousu Mendy; Gregorius Sri Nurhartanto (TRUNOJOYO LAW REVIEW, 2026)
This study aims to examine the institutional design of the newly established Constitutional Court of Pakistan under the 27th Constitutional Amendment to the 1973 Constitution through a comparative analysis with the Constitutional Court of Indonesia, focusing on judicial independence, accountability, and the protection of constitutional rights. The contribution of this research lies in providing a comparative constitutional law perspective on the compatibility of Pakistan’s new constitutional adjudication framework while identifying institutional lessons from the Indonesian model. This study employs normative legal research using descriptive and prescriptive approaches. The findings show that establishing a specialized Constitutional Court can strengthen constitutionalism, democracy, and the protection of fundamental rights. However, several provisions introduced by the 27th Constitutional Amendment raise concerns regarding judicial independence, accountability, and the right to a fair trial. The comparative analysis indicates that the Indonesian Constitutional Court provides a more balanced framework for safeguarding judicial autonomy while maintaining institutional accountability through constitutional mechanisms. This study concludes that, although the establishment of the Constitutional Court represents a significant constitutional development in Pakistan, certain aspects of its institutional arrangement remain inconsistent with international human rights obligations and universally recognized standards of judicial independence. Therefore, the amendment should be subject to constitutional review and reform to ensure conformity with Pakistan’s international commitments. It is recommended that the Constitutional Court adopt a rights-based interpretative approach grounded in the International Bill of Rights and strengthen the constitutional principles of equality and non-discrimination as fundamental norms guiding constitutional adjudication and the protection of human rights.